A new model for DOA estimation and its solution by multi-target intermittent particle swarm optimization. (1st April 2021) - Cui, Lizhi; Zhao, Peichao; Li, Xinwei; Li, Bingfeng; Wang, Keping; Bu, Xuhui; Fei, Shumin; Yang, Yi
Abstract : Currently, the widely used methods for direction of arrival (DOA) estimation were constructed based on the subspace, such as Multiple Signal Classification (MUSIC) and Estimating Signal Parameter via Rotational Invariance Techniques (ESPRIT), which required that the number of sources is known beforehand. In this paper, a new method based on the Vector Error Model (VEM) for estimating the DOAs was proposed, which do not need the sources number in advance. The comparison of the performance between the VEM and the MUSIC model for DOA problem was given to demonstrate the effectiveness of our method. The algorithm of multi-target intermittent particle swarm optimization (MIPSO) was adopted to solve the VEM, and the performance of the VEM-MIPSO method was analysed through simulations for a uniform linear array and an L-shaped array respectively. The results showed that: (1) the VEM was an effective model to solve the DOA estimation without prior knowledge of the sources number; (2) the MIPSO was an efficient algorithm to solve the DOA estimation with high precision.